The Psychometric Properties of the Norwegian version of Assessment, Intervention and Moving On (AIM3); the assessment model - Borren, Ingrid; Skar, Ane-Marthe Solheim (PsykTestBarn, 2024)
Description: Assessment, Intervention and Moving On (AIM) is an interdisciplinary, guiding framework for professionals who work with children and young people up to the age of 18 with problematic sexual behavior (PSB) or harmful sexual behavior (HSB). AIM1 was first introduced in 2002 by Henniker, Print & Morrison in the AIM project group from Great Britain (international license holder). The AIM framework consists of several elements suitable for both identification and treatment of PSB/HSB, including an AIM checklist, an AIM assessment tool, and the AIM intervention guide. The AIM assessment tool has been revised twice and the latest version, AIM3, was introduced in 2019 and translated to Norwegian in 2020 by Ressursenheten V27, Betanien hospital (Norwegian license holder) and Regional centre on violence, traumatic stress and suicide prevention (RVTS) North. The focus of this paper is on the assessment tool of AIM3.The AIM3 assessment model focuses on 5 domains with 5 factors (items) each (25 factors in total) indicating degree of concern. The intervention guide is not a manualized treatment plan but facilitates individually customized treatment based on the recommendations from the AIM3 assessment. Only certified professionals who have participated in the AIM3 course and completed a competency test can use the AIM3 assessment tool. The assessment tool courses target employees in special health services, family services, child advocacy centers, child welfare, school nurses, municipal psychologists, conflict councils, and correctional services. Literature search: The literature search resulted in one included Norwegian article. The participants in this study were 56 Norwegian professionals recruited at AIM3 courses who scored three case vignettes (composed cases based on previous anonymized real cases). Hence, the documentation does not include psychometric information from any real population. Psychometrics: The results showed that the AIM3 has moderate intraclass correlations based on scoring of the case vignettes; 0.55 (95% CI = 0.47, 0.63) for the factor score, full scale (all 25 factors x 3 case vignettes x 56 professionals) and ICC 0.70 (95% CI = 0.55, 0.85) for the domain score (sum scores for all five domains x 3 case vignettes x 56 professionals). Conclusion: The literature screening showed that there is a lack of Norwegian and Scandinavian studies on any population (only data from scoring of case vignettes) that describe the psychometric properties of AIM3 as utilized in Norwegian context. No conclusions can hence be drawn on the psychometric properties of AIM3.